2020
DOI: 10.21608/dsu.2020.30956.1038
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Resveratrol with 5-Fluorouracil in Chemotherapy of Induced Oral Squamous Cell Carcinoma

Abstract: Introduction: Oral cancer is a common cause of death in human, its treatment involves chemotherapy. However, toxicity is an obstacle to this treatment. Studies suggested that combining chemotherapy with specific antioxidants can improve drug efficacy and reduce the chemotherapeutic drug toxicity. Aim: To evaluate the anticancer effect of resveratrol alone or combined with 5-Fu on experimentally induced tongue cancer. Materials and Methods: Forty male albino rats were divided into five groups: Group I: untreate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Also RES can increase the number of S phase cells that is a reason why the produced synergy effect increased the percentage of apoptotic cells, activated the level of caspase-3, cleaved PARP and p53 protein and finally increased the Bax/Bcl-2 ratio [85]. The synergy effect on the oral squamous cell carcinoma and the combined therapy had regressed this affection to mild dysplasia [86]. In colon cancer the combination showed attenuation of injury severity.…”
Section: Combination Of Piperine Curcumin Resveratrol and Icariin Wit...mentioning
confidence: 99%
“…Also RES can increase the number of S phase cells that is a reason why the produced synergy effect increased the percentage of apoptotic cells, activated the level of caspase-3, cleaved PARP and p53 protein and finally increased the Bax/Bcl-2 ratio [85]. The synergy effect on the oral squamous cell carcinoma and the combined therapy had regressed this affection to mild dysplasia [86]. In colon cancer the combination showed attenuation of injury severity.…”
Section: Combination Of Piperine Curcumin Resveratrol and Icariin Wit...mentioning
confidence: 99%
“…The 5-Fluoro-2,4(1H,3H)-pyrimidinedione (5-FU) family, commercially known as Fluorouracil are antimetabolite drugs that work by inhibiting essential biosynthetic processes, or by being incorporated into macromolecules, such as DNA and RNA, resulting in inhibition of their normal function [7,8]. It is a pyrimidine analogue that was first discovered in 1957 and remains a crucial chemotherapeutic drug for various solid tumors including OSCC [7,9].…”
Section: Research Articlementioning
confidence: 99%
“…It is converted intracellularly to several active metabolites: fluorodeoxyuridine monophosphate (FdUMP), fluorodeoxyuridine triphosphate (FdUTP), and fluorouridine triphosphate (FUTP). These active metabolites disrupt RNA synthesis and the action of thymidylate synthase (TS) [7,9,8]. Moreover, the toxic side effects that accompany therapeutic dosages of 5-FU have limited its systemic use in tumor therapy [6].…”
Section: Research Articlementioning
confidence: 99%
“…10 rats were intraperitoneally injected with a single dose of freshly prepared DEN (200 mg/kg b.w), 2 weeks later, they were subcutaneously injected with CCl 4 once weekly (3 mL/ kg b.w) for 6 weeks to enhance DEN carcinogenicity as a model for liver cancer (Aboubakr et al, 2017;El-Tabl et al, 2019). 30 rats received DEN as in the previous group, and then treated either with 5-FU or RES or both of them as following; 10 HCC animals were intraperitoneally injected by 5-Fluorouracil (12.5mg/kg, 3 days weekly (day after day) for 2 months) (Soliman et al, 2018), 10 HCC-rats were orally administrated resveratrol dissolved in DMSO (200 μg/kg b.w daily for 2 months) (Soliman et al, 2018;El-Oraby et al, 2020), and 10 HCC rats treated with both 5-FU and RES (6.25 mg 5-FU/kg (ip) on days 1, 3, and 5 of the week for 2 months, and in the same period, rats were daily oral given 100μg RES/kg).…”
Section: Experimental Designmentioning
confidence: 99%
“…Adikwu et al (2019) reported that RES had a therapeutic benefit in nephrotoxicity in rats caused by 5-FU, which further elucidates the protective impact of RES on normal cells. El-Oraby et al (2020) reported the synergistic impacts of resveratrol with 5-fluorouracil against oral squamous cell carcinoma in rats.…”
Section: Introductionmentioning
confidence: 99%